Akta wizytacyjne Diecezji Kamienieckiej i Łucko-Żytomierskiej (koniec XVIII-początek XX wieku) w zasobach archiwów na Ukrainie - Rosowski, Witalij (Archiwa, Biblioteki i Muzea Kościelne, 2020)
Visitations are one of the most valuable and interesting church sources. This article attempts to present the condition of visitation records of churches and monasteries of the Diocese of Lutsk-Zhytomyr and Kamyanyets from the late 18th to the early 20th century in the archives of Ukraine. Difficult history of these lands in the last century contributed to a considerable dispersal of interesting materials, and what is worse, to irreversible destruction of some of the records. Currently, the largest number of the visitation descriptions of the mentioned dioceses are preserved in the Central State of Historical Archive of Ukraine in Kyiv and the State Archive of Zhytomir and Khmelnytskyi Oblast, which include, among others, the fonds of the Roman-Catholic Consistory of Kamyanyets and Lutsk-Zhytomyr and the visitation records of the monasteries in the Diocese of Lutsk-Zhytomyr. The presented material showed that the oldest of the surviving visitation records of the churches and monasteries in Podolia, Volhynia and the Kiev region come from the mid-90s of the 18th century and the latest ones come from 1909.